Status Kepemilikan Dan Pemanfaatan Tanah Grondkaart Di Stasiun Depok Baru, Lenteng Agung, Dan Tanjung Barat - Sulistiowati, Sulistiowati; Ismail, Nurhasan; Rahman, Taufiq El (UI Scholars Hub, 2020)
The disputes over land ownership and utilization of Grondkaart for Railway activities between the government and PT KAI should not have occurred due to both having the same vested interest for the state. However, the reality shown that land ownership dan agreement status on land use with the third party. Through the qualitative analysis, the research findings: First, land originating from Grondkaart at the location still belongs to the goverment due to the land still holding the status of the right to use or Hak Pakai during the course of the time the land used by the Government and the land participation as a capital in PT KAI before the process of handling the right of land ownership; Second, there is a difference in the legalty of the land use agreement with a third party, namely the agreement made by PT KAI that does not fulfill 2 (two) legal requirements within the agreement, namely the ability to act and on the agreement and the legality of the clauses, meanwhile the agreement taht should be enacted by the government should fulfill all the valid requirements of the agreement.